Sulfonyl pyrazoles as sustainable dual functional group transfer reagents: AlCl3 promoted transfer of sulfonyl and pyrazole groups - Kour, Harpreet; Mahajan, Shivangani; Ahmed, Sumeer; Birajdar, Ram; Verma, Praveen Kumar; Singh, Parvinder Pal; Sawant, Sanghapal D. (Journal of Organic Chemistry, 2026)
Herein, we report sulfonyl pyrazoles as sustainable dual-functional group transfer reagents for the transfer of two different functional groups to two different acceptors under mild conditions facilitated by AlCl3. The transformation proceeds via two distinct transition states: in the first, AlCl3 activates the S-N bond toward cleavage, and in the second, a sulfoximine nucleophilically attacks the sulfonyl group, resulting in the elimination of the pyrazole moiety. This process yields sulfonyl amidines, compounds with significant medicinal relevance, while the liberated pyrazole effectively participates in subsequent reactions with Michael acceptors. Notably, the protocol operates without the need for transition-metal catalysts and exhibits broad substrate scope along with excellent functional group tolerance.